Extracorporeal membrane oxygenation in children receiving haematopoietic cell transplantation and immune effector cell therapy: an international and multidisciplinary consensus statement. (February 2022) - Di Nardo, Matteo; Ahmad, Ali H; Merli, Pietro; Zinter, Matthew S; Lehman, Leslie E; Rowan, Courtney M; Steiner, Marie E; Hingorani, Sangeeta; Angelo, Joseph R; Abdel-Azim, Hisham; Khazal, Sajad J; Shoberu, Basirat; et al.
Summary: Use of extracorporeal membrane oxygenation (ECMO) in children receiving haematopoietic cell transplantation (HCT) and immune effector cell therapy is controversial and evidence-based guidelines have not been established. Remarkable advancements in HCT and immune effector cell therapies have changed expectations around reversibility of organ dysfunction and survival for affected patients. Herein, members of the Extracorporeal Life Support Organization (ELSO), Pediatric Acute Lung Injury and Sepsis Investigators (PALISI) Network (HCT and cancer immunotherapy subgroup), the Pediatric Diseases Working Party of the European Society for Blood and Marrow Transplantation (EBMT), the supportive care committee of the Pediatric Transplantation and Cellular Therapy Consortium (PTCTC), and the Pediatric Intensive Care Oncology Kids in Europe Research (POKER) group of the European Society of Pediatric and Neonatal Intensive Care (ESPNIC) provide consensus recommendations on the use of ECMO in children receiving HCT and immune effector cell therapy. These are the first international, multidisciplinary consensus-based recommendations on the use of ECMO in this patient population. This Review provides a clinical decision support tool for paediatric haematologists, oncologists, and critical care physicians during the difficult decision-making process of ECMO candidacy and management. These recommendations can represent a base for future research studies focused on ECMO selection criteria and bedside management.